Success factors that enhance the export performance of industrial smes mexicanas (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2015)
Recent studies have pointed that an environment that favors the exportation performance, is the appealing of international markets to exchange products and increase SEM's competitiveness. In the literature, the export performance measurement constitutes one of the most controversial facts regarding the exports management; therefore, different theories and models will be investigated to explain the internationalization process that SEM's perform through different approaches and perspectives. In that sense, shall be determined the success factors that improve the performance of Mexican industrial SME's, in such manner that allows them to develop and promote their exportation in order to become more competitive worldwide for which a measurement instrument of Likert's five points scale, was designed and applied in a pilot test to 30 subjects, which allowed to calculate its reliability, through the Cronbach's alpha coefficient for the five independent variables identified in the literature: price (X1 = 0.897); quality (X2 = 0.893); installed capacity (X3 = 0.820); innovation (X4 = 0.836) and financial capacity (X5 = 0.766); while for the exporting factor (Y) the result was 0.758. The variables introduced (X5, X1), explained in a 74.5% (R2 = 0.745) the variability in the answer's variable (Y), while the benevolence of the linear model adjusted was enough and significant in P (value) < 0.05, concluding there is enough evidence in the theoretical framework to sustain the results obtained through the regression model
Keywords: exports performance; exportations; internationalization; industrial sem's